613 HER2-XPAT, a novel protease-activatable prodrug T cell engager (TCE), with potent T-cell activation and efficacy in solid tumors and large predicted safety margins in non-human primate (NHP). (10th December 2020) - Cattaruzza, Fiore; Nazeer, Ayesha; Lange, Zachary; Koski, Caitlin; Hammond, Mikhail; Dao-Pick, Trang; Henkensiefken, Angela; Derynck, Mika; Schellenberger, Volker; Irving, Bryan
Abstract : Background: TCEs are effective in leukemias but have been challenging in solid tumors due to on-target, off-tumor toxicity. Attempts to circumvent CRS include step-up dosing and/or complex designs but are unsuccessful due to toxicity and/or enhanced immunogenicity. HER2-XPAT, or X TENylated P rotease-A ctivated bispecific T -Cell Engager, is a prodrug TCE that exploits the protease activity present in tumors vs. healthy tissue to expand the therapeutic index (TI). The core of the HER2-XPAT (PAT) consists of 2 tandem scFvs targeting CD3 and HER2. Attached to the core, two unstructured polypeptide masks (XTEN) sterically reduce target engagement and extend T1/2. Protease cleavage sites at the base of the XTEN masks enable proteolytic activation of XPATs in the tumor microenvironment, unleashing a potent TCE with short T1/2, further improving the TI. HER2-XPAT, a tumor protease-activatable prodrug with wide safety margins, can co-opt T-cells regardless of antigenic specificity to induce T-cell killing of HER2+ tumors. Methods: Preclinical studies were conducted to characterize the activity of HER2-XPAT, HER2-PAT (cleaved XPAT), and HER2-NonClv (a non-cleavable XPAT) for cytotoxicity in vitro, for anti-tumor efficacy in xenograft models, and for safety in NHPs. Results: HER2-PAT demonstrated potent in vitro T-cell cytotoxicity (EC50 1-2pM) and target-dependent T-cell activation and cytokine production by hPBMCs. HER2-XPAT provided up to 14, 000-fold protection against killing of HER2 tumor cells and no cytotoxicity against cardiomyocytes up to 1uM. In vivo, HER2-XPAT induced complete tumor regressions in BT-474 tumors with equimolar dosing to HER2-PAT, whereas HER2-NonClv had no efficacy, supporting requirement of protease cleavage for T-cell activity. In NHP, HER2-XPAT has been dose-escalated safely up to 42mg/kg (MTD). HER2-XPAT demonstrated early T-cell margination at 2 mg/kg but largely spared CRS, cytokine production, and tissue toxicity up to 42 mg/kg. PK profiles of HER2-XPAT and HER2-NonClv were comparable, consistent with ex vivo stability for cleavage when incubated in cancer pts plasma for 7 days at 37°C. HER2-PAT by continuous infusion induced lethal CRS and cytokine spikes at 0.3 mg/kg/d but was tolerated at 0.25 mg/kg/d, providing HER2-XPAT with >1300-fold protection in tolerability vs. HER2-PAT, >4 logs over cytotoxicity EC50s for HER2 cell lines, and a 20-fold safety margin over the dose required for pharmacodynamic activity. Conclusions: HER2-XPAT is a potent prodrug TCE with no CRS and a wide TI based on NHPs. With XTEN's clinical data demonstrating low immunogenicity, the XPATs are a promising solution. IND studies are ongoing. Additional PK/PD, cytokines, safety, and efficacy data will be presented.